2018
DOI: 10.1002/jcla.22595
|View full text |Cite
|
Sign up to set email alerts
|

Association of single nucleotide polymorphisms in resistin gene with rheumatoid arthritis in a Chinese population

Abstract: In a ward, our results indicated that resistin gene polymorphisms might affect the genetic predisposition of RA in Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…This finding disagrees with the study in China. 24 The results of this current study revealed that CRP did not correlate with resistin. This could be due to the observation being made during the period of treatment.…”
Section: Discussioncontrasting
confidence: 46%
“…This finding disagrees with the study in China. 24 The results of this current study revealed that CRP did not correlate with resistin. This could be due to the observation being made during the period of treatment.…”
Section: Discussioncontrasting
confidence: 46%
“…Accordingly, a downregulation of resistin gene expression in CD4 Th lymphocytes and CD14 monocytes in RA patients responding to TNF-α inhibitor therapy has recently been demonstrated, showing an increased expression in patients who failed to respond to the therapy [166]. In addition, recent studies in a Chinese population have demonstrated the association of SNP in the resistin gene with RA susceptibility as well as with its clinicopathological characteristics [167,168].…”
Section: Resistinmentioning
confidence: 99%